The Potency of Capa Plant (Blumea balsamifera L.) as a Source of Wound Medicine : Systematic Review - Khalisah Khalisah; Masyudi Masyudi; Saudah Saudah; Jailani Jailani; Irhamni Irhamni (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Background: Blumea balsamifera L., locally known as CAPA, has long been used by the people of Aceh for various traditional treatments, particularly wound healing. In South Aceh, the leaves are commonly applied topically by squeezing the juice directly onto injured skin. Previous studies indicate that excessive use of chemical wound medications may cause allergic reactions, dryness, and delayed wound healing. The World Health Organization (WHO) also recommends the utilization of traditional medicines, including herbal remedies, for public health maintenance. Objectives: This study aims to review the potential of Blumea balsamifera L. as a wound healing agent and to assess its feasibility for development into a gel-based topical formulation. Methods: A literature review was conducted by collecting 100 articles related to the medicinal use of Blumea balsamifera L. From these, selected articles specifically discussing its application for wound healing were analyzed. Sources were obtained from indexed international journals and SINTA-accredited national journals, followed by a discussion of a proposed research plan for CAPA leaf extract gel formulation. Results: The reviewed studies indicate that Blumea balsamifera L. possesses antibacterial and anti-inflammatory properties and shows strong potential to be developed as a wound healing agent in gel form, which supports effective drug delivery and wound moisture balance. Conclusion: Blumea balsamifera L. is a promising natural alternative for wound healing. The development of a gel-based formulation may provide a safe, practical, and effective approach that aligns with modern wound care principles and supports the use of traditional medicinal plants.